2014
DOI: 10.1063/1.4901923
|View full text |Cite
|
Sign up to set email alerts
|

Electron states in semiconductor quantum dots

Abstract: In this work, the electronic structures of quantum dots (QDs) of nine direct band gap semiconductor materials belonging to the group II-VI and III-V families are investigated, within the empirical tight-binding framework, in the effective bond orbital model. This methodology is shown to accurately describe these systems, yielding, at the same time, qualitative insights into their electronic properties. Various features of the bulk band structure such as band-gaps, band curvature, and band widths around symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Quantum size effects in the traditional chalcogenide semiconductor QDs arising from the three-dimensional confinement of the charge carriers have been extremely well studied , and lead to many interesting applications. In contrast, studies on quantum size effects of these perovskite materials are quite rare .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum size effects in the traditional chalcogenide semiconductor QDs arising from the three-dimensional confinement of the charge carriers have been extremely well studied , and lead to many interesting applications. In contrast, studies on quantum size effects of these perovskite materials are quite rare .…”
Section: Resultsmentioning
confidence: 99%
“…The optical transitions between the occupied and unoccupied Kohn–Sham states were calculated for the ground state geometries using density functional perturbation theory (DFPT). For each of the ligated QDs, the exciton Bohr radius ( a B ) and the exciton binding energies were calculated using the following equations: where a B = exciton Bohr radius, ϵ = dielectric constant of the material, μ* = reduced mass = m h m e /( m h + m e ), m h = effective mass of hole, m e = effective mass of electron, m 0 = mass of electron, E g = bulk band gap, R = radius of the QD and e = charge of the electron.…”
Section: Introductionmentioning
confidence: 99%
“…While a qualitative picture of these shifts may be obtained from Effective Mass theory 59 , a detailed understanding requires a more sophisticated theory, such as tight binding (TB) theory, which includes band non-parabolicity and band-mixing effects. Using TB theory, the size dependence of the electronic spectra, exciton peaks and absorption spectra of bare QDs for various sizes and materials have been studied earlier [60][61][62] . While DFT calculations could in principle also yield the quantum size effects accurately, these are presently far too expensive to carry out for all but the smallest QDs.…”
Section: Size Determination Of Qdsmentioning
confidence: 99%
“…Using TB theory, the size dependence of the electronic spectra, exciton peaks and absorption spectra of bare QDs for various sizes and materials have been studied earlier. [60][61][62] While DFT calculations could in principle also yield the quantum size effects accurately, these are presently far too expensive to carry out for all but the smallest QDs. The experimental optical absorption spectra of the cleaned QD samples (bare QDs with passivating agents attached) in this study are shown in Fig.…”
Section: Size Determination Of Qdsmentioning
confidence: 99%
“…5 (a) shows absorption and photoluminescence spectra of colloidal solution of CdS QDs. Whereas, Dhayal et al [27] have reported that there are real excited states at this energy level for CdS QDs. Therefore, it can be concluded that the electrons absorb three-photons initially and reach these real excited states.…”
Section: Resultsmentioning
confidence: 90%